2016
DOI: 10.1039/c5ee02393a
|View full text |Cite
|
Sign up to set email alerts
|

Multijunction Si photocathodes with tunable photovoltages from 2.0 V to 2.8 V for light induced water splitting

Abstract: 9We report on the development of high performance triple and quadruple junction solar cells 10 made of amorphous (a-Si:H) and microcrystalline silicon (µc-Si:H) for the application as 11 photocathodes in integrated photovoltaic-electrosynthetic devices for solar water splitting. We 12 show that the electronic properties of the individual sub cells can be adjusted such that the 13 photovoltages of multijunction devices cover a wide range of photovoltages from 2.0 V up to 14 2.8 V with photovoltaic efficiencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
176
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 187 publications
(177 citation statements)
references
References 48 publications
1
176
0
Order By: Relevance
“…The obtained results can then be applied to further optimize devices based on multijunction solar cells. [2][3][4][5][6] Especially in the last few years, there have been a lot of great accomplishments in this direction. McDowell and Hu 7,8 investigated the performance of n-Si | TiO 2 heterojunctions and TiO 2 covered np + homojunctions with an additional Ni catalyst, achieving good long term stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results can then be applied to further optimize devices based on multijunction solar cells. [2][3][4][5][6] Especially in the last few years, there have been a lot of great accomplishments in this direction. McDowell and Hu 7,8 investigated the performance of n-Si | TiO 2 heterojunctions and TiO 2 covered np + homojunctions with an additional Ni catalyst, achieving good long term stability.…”
mentioning
confidence: 99%
“…The obtained results can then be applied to further optimize devices based on multijunction solar cells. [2][3][4][5][6] …”
mentioning
confidence: 99%
“…The development of the tandem , triple , and quadruple junction solar cells used in this is study is described elsewhere. The solar cells were particularly developed according to the requirements for the application as photocathodes in a solar water splitting device.…”
Section: Methodsmentioning
confidence: 99%
“…Using light concentration Fujii et al showed >12% on a large area including a membrane for product separation [27]. catalysts [28]. Stellmach et al have reached 2.5% with the noble metal free HER catalyst MoS 2 catalyst in a complete wireless 'artificial leaf' configuration [29].…”
Section: Group (Ii A) 'Back-back-multi'mentioning
confidence: 98%